Pengaruh Pembelajaran Inkuiri Terhadap Kemampuan Berpikir Kritis Siswa SMA Negeri 02 Bengkulu utara - Erwani Yusuf; Gustiyana Gustiyana (Jurnal Multidisiplin Dehasen (MUDE), 2022)
The critical thinking ability of students at SMA Negeri 02 Bengkulu Utara is still relatively low. For this reason, it is very necessary to have a learning system that supports the improvement of students' critical thinking skills. The inquiry learning emphasizes the activeness of students to have a learning experience in finding material concepts based on the problems posed so that they can improve students' critical thinking skills. The purpose of this study is to determine the critical thinking skills of students at SMA Negeri 02 Bengkulu Utara and to determine the effect of inquiry learning on students' critical thinking skills at SMA Negeri 02 Bengkulu Utara. The type of research conducted is experimental research. The research methodology used in this research is quantitative, namely quasi-experimental. Data collection analysis techniques through tests, observations and documentation. The samples taken are class X MIPA 5 and X MIPA 6. Where the number of students in class X MIPA 5 is 30 people and class X MIPA 6 is 30 people. The results of this study indicate that inquiry learning at SMA Negeri 02 Bengkulu Utara has an influence on students' critical thinking skills, this can be seen from the results of testing the calculated f value (3.150) more than f table (0.05) so that based on the testing criteria, the null hypothesis (H0) is rejected. There is no difference in the initial critical thinking ability of students at SMA Negeri 02 Bengkulu Utara for the experimental class and the control class, this can be seen from the tcount value less than ttable so that the null hypothesis is accepted. Meanwhile, for students' critical thinking skills for the experimental class and the control class after being given treatment there are differences, this can be seen from the value of tcount more than ttable, the null hypothesis is rejected. The effect of inquiry learning on students' critical thinking skills at SMA Negeri 02 Bengkulu Utara shows the average N-gain score for the experimental class of 60.87% "Quite effective". Meanwhile for the control class, 36.09% is "ineffective". So it can be concluded that the use of the inquiry learning model is quite effective in improving students' critical thinking skills at SMA Negeri 02 Bengkulu Utara. .